134k views
2 votes
Plzzzz help

1) Given f(x)=x+4 and g(x)=12x-6, what is f(3)+g(-1)?

A.) 22
B.) 33
C.) -11
D.) 11

2) what is f(x).g(x) if f(x)= 2x+3 and g(x)=4x?
A) 6x+3
B) 6x^2+12
C) 8x^2+12
D) 8x+3

3) f(x)=2x-3 and g(x)=4x what is f(2)-g(3)

A) 15
B) -11
C) -15
D) -5

User Epitka
by
5.0k points

2 Answers

2 votes

Answer:

1) C.) -11

2) C.) 8x² + 12x

3) B) -11

Explanation:

1)

f(x) = x + 4

f(3) = 3 + 4 = 7

g(x) = 12x - 6

g(-1) = 12(-1) - 6 = -12 - 6 = -18

f(3) + g(-1) = 7 + (-18) = -11

2)

f(x) = 2x + 3, g(x) = 4x

f(x) · g(x) = (2x + 3)(4x) use the distributive property

f(x) · g(x) = (2x)(4x) + (3)(4x)

f(x) · g(x) = 8x² + 12x

3)

f(x) = 2x - 3

f(2) = 2(2) - 3 = 4 - 3 = 1

g(x) = 4x

g(3) = 4(3) = 12

f(2) - g(3) = 1 - 12 = -11

User Bulla
by
6.4k points
0 votes

1) Given f(x)=x+4 and g(x)=12x-6, what is f(3)+g(-1)?

C) -11

2) what is f(x).g(x) if f(x)= 2x+3 and g(x)=4x?

C) 8x^2+12

3) f(x)=2x-3 and g(x)=4x what is f(2)-g(3)

B) -11

User NLindros
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.